Welfare Evaluation of the 1986 Tax Reform for Married Couples in the United States - Matteo Picchio; Giacomo Valletta (Institute for the Study of Labor (IZA), 2015)
This paper evaluates the welfare effects of the 1986 Tax Reform Act (TRA86). In thirty years since its introduction, several studies have analysed the effects of TRA86. However, preference heterogeneity and non-market dimensions of welfare have not been taken into account. We propose an evaluation of the impact of TRA86 on well-being using different welfare metrics which fully retain preference heterogeneity. We estimate utility functions with preference heterogeneity on the basis of structural models of family labor supply. Then, by way of these estimated preferences, we compute several welfare rankings corresponding to different ethical priors. Finally, we identify the losers and the winners of TRA86 under different ethical priors.
Keywords: C25; D63; H22; H31; J22; 330; welfare measures; tax reform; preference heterogeneity; discrete model; labor supply